Formulation development and evaluation of novel oral jellies of carbamazepine using pectin, guar gum, and gellan gum - Prakash, Dr. Katakam (Asian Journal of Pharmaceutics (AJP), 2014)
Medicated jelly formulations are more suitable for pediatric, geriatric and dysphagic patients, which offer rapid dissolution and absorption of drugs thereby early onset of action. The aim was to develop and evaluate oral jellyÂ formulations of carbamazepine (CBZ). Carbamazepine oral jellies were prepared to employ pectin, guar gum and gellanÂ gum alone and pectinâ€guar gum combination. Preformulation studies, organoleptic, physical characteristics, drug content,Â pH, spreadability, rheological properties, syneresis, taste masking, in vitro dissolution testing, drug release kinetics andÂ stability studies were conducted. The Fourier transform infrared and differential scanning calorimeter studies showed thatÂ there was no interaction between drug and excipients. The pH of all the formulations was found between pH 6.37 Â± 0.03Â and 6.83 Â± 0.04. The concentration of gelling agents influenced the spreadability. Syneresis was observed in jellies madeÂ from guar gum alone, whereas those made from pectin and guar gum it was absent. The optimized formulations (F3, F11Â and F15) masked the bitter taste of CBZ and demonstrated acceptable flavor and mouth feel. All formulations showed moreÂ than 50% drug release in 15 min except those made of gellan gum alone. The formulations F3, F11 and F15, were foundÂ stable for 90 days as per International Conference on Harmonization stability protocol. Carbamazepine jellies made from pectin (F3, 1.2%), gellan gum (F11, 1.5%) and pectinâ€guar gum (F15, 1:0.4%) were found more successful and could be employed to improve the palatability and acceptability by pediatric, geriatric and dysphagic patients. The jellies could be useful to overcome the problems of poorly soluble CBZ. Key words: Carbamazepine, dysphagic patients, medicated jelly, natural polymers